Investigating the impact of web-based language learning (WBLL) through write & improve on writing skills in secondary school - Shermilya A. Rodzi; Noraini binti Said (Penerbit UMS, 2024)
This study examines the impact of Web-Based Language Learning (WBLL) using the program Write & Improve on secondary school students' writing skills at SM St. Michael, Penampang, using the Social Cognitive Theory (SCT). The study sought to investigate students' perspectives and impact in writing through guided practice and feedback. The researcher used a two-cycle action research design that included both writing activities and open-ended surveys to collect information about students' writing performance and perceptions. Initial studies revealed that students struggled with the tool's UI and feedback mechanisms, restricting their development throughout the first cycle. However, significant increases were seen in the second cycle, with students obtaining higher CEFR bands and showing a greater grasp of feedback. Surveys revealed high satisfaction and perceived the effectiveness of Write & Improve, despite some technical issues and occasional inaccuracies in feedback. The study emphasizes the significance of teacher participation, as SCT and Vygotsky's Zone of Proximal Development (ZPD) indicate that directed learning and feedback can improve student outcomes. Researchers should conduct longitudinal investigations and perform different demographic testing. For educators, the findings emphasize optimal practices for incorporating WBLL technologies into instruction. This study adds to the growing body of knowledge about digital learning aids as well as providing ideas for better writing teaching through technology.